VALUES IN A MODERN FAMILY. BETWEEN DECLARATION AND DEED - Zalewska, Sabina Lucyna (Society Register, 2017)
Values are such multiform phenomenon that they can be considered in numerous aspects, depending on the point of view and methods of research. They can be considered from the philosopher, psychologist, ethnographer, culture anthropologist, sociologist or economist point of view. However, in the frames of the elaboration, the topic is seen from the pedagogical and psychological aspect of what we call a value. A value can be considered as a phenomenon of choosing an aim, assuming an attitude towards the aim, selection of alternative aspirations in a certain psychological situation, selection of needs, means of action. Assuming a family as a fundamental unit of society we can conclude that values work similarly in a family. Spouses understand each other better when they both assent the same basic values. Common values is the factor of constancy and development of marriage in the periods of crisis. Spouses, thanks to creation a common hierarchy of values, build between them a deep bond, asserting the most important values as the common ones, recognize their differences in the less important ones, as well as they respect each other’s variety of the lowest values in their values hierarchy, being aware of their enriching effect on the marital community. All over the world we can deal with values presented by somebody or something. While choosing a certain value a man attributes it to somebody or something and based on it choses between competitive objects. While attributing a value a man uses an evaluation to establish a valence of the object. In other words, we value if we prize certain things more than others. Values can refer to understanding one good for a unit or society, which is worth implementing.